Examining student-designed games through Suits' theory of games. Issue 8 (16th November 2016) - Casey, Ashley; Hastie, Peter; Jump, Steve
Abstract : This paper documents how a unit of student-designed games can create a more meaningful version of physical education (PE) for disengaged students, a version that enhances the educational legitimacy of the subject matter by affording it worth in and of itself rather than being justified for other, extrinsic or instrumental reasons. Furthermore, it seeks to develop new knowledge relating to the conduct of game instruction within PE, by using Suits' theory of games. Drawing on Suits' theory, we develop a conceptual model that is intended to represent the hierarchical processes that occur in gameplay through student-designed games. This model is then tested via examination of the experiences of a cohort of teachers and their year 10 students from a mixed secondary school in the greater London area. From our discussions with the students, it is argued that the key focus of the games that these students were used to playing was the need to 'play the game well'. By contrast, we suggest that it is possible to provide more meaningful experiences to students if a more philosophically driven and less efficiency-driven approach to games is taken, following Suits' lead more closely. By exploring the loop between and around lusory means, lusory goals and constitutive rules (the aspects of Suits' theory that have been shown to represent student-designed games), students engage with a more meaningful games experience than simply playing the game well. This 'new' approach to games may offer counterbalance to the ideological tendencies now emphasized in countries and contexts that celebrate instrumental outcomes of performative PE and sport rather than affording worth in and of itself to the curriculum's subject matter.